Pelatihan Debat Parlementer Untuk Meningkatkan Motivasi Santri Dalam Berbicara Bahasa Inggris - Sukma Septian Nasution; Bambang Irawan; Abdul Aziz; Asep Ahmad; Suwardi Suwardi (JPM: Jurnal Pengabdian Masyarakat, 2020)
The significnce of speaking in English has triggered education practitioners to organize an English program as done by Madrasah Aliyah Nurul Qur’an. However, observation result reveals that students of the school face some difficulties in speaking English such as limited arrange of vocabulary, mispronouncing, and self confidence. Accordingly, a team from English Literature Study Program of Universitas Pamulang initiated to conduct a community service to improve the students’ speaking skill by using parliamentary debate with the following steps: (1) presenting the students a set of materials about parliamentary debate; (2) grouping the students, (3)some groups act as affirmative group and the others as opposition; (4) motivating and sharing some tips to be proficient in English. The afore-mentioned steps are meant to brace the students to be more confident and motivated in speaking English.